Influence of Particle Shape on the Macroscopic and Mesolevel Mechanical Properties of Slip Zone Soil Based on 3D Scanning and 3D DEM. (9th October 2021) - Li, Zechuang; Liu, Zhibin
Abstract : The macroscopic and mesolevel mechanical mechanisms of slip zone soil are a crucial subject for the research of landslide deformation evolution and slope control, but the effects of the shape and psephicity of coarse particles in a slip zone soil on the mechanical properties of the slip soil zone still need to be explored. Discrete element method (DEM) can effectively monitor and track the mesolevel mechanical parameters of geotechnical materials, such as displacement vector field, contact force chain, and particle coordination number. The rock blocks in the medium-sized shear test undergo a sophisticated process by 3D scanning technology, and a database of the blocks is established and accurately modeled by combining 3D DEM to simulate the indoor medium-sized shear test for numerical investigation in line with the test conditions. The numerical simulation results demonstrate that the psephicity and particle shape of the rock blocks significantly affect the dilatancy and mesolevel mechanical parameters of the slip zone soil specimens. In addition, the numerical models featured by poorer psephicity and more irregular particle shape display more evident dilatancy, larger particle coordination numbers, as well as better contact density inside the model. Some references for the study of the macroscopic and mesolevel mechanical mechanisms of slip zone soil are provided.